2022
DOI: 10.3390/ijms23052659
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Gastro-Duodenal Effect on Adipose Tissue and Brain Metabolism, Potentially Mediated by Gut–Liver Inflammation: A Study with Positron Emission Tomography and Oral 18FDG in Mice

Abstract: Interventions affecting gastrointestinal (GI) physiology suggest that the GI tract plays an important role in modulating the uptake of ingested glucose by body tissues. We aimed at validating the use of positron emission tomography (PET) with oral 18FDG administration in mice, and to examine GI effects on glucose metabolism in adipose tissues, brain, heart, muscle, and liver, and interfering actions of oral lipid co-administration. We performed sequential whole-body PET studies in 3 groups of 10 mice, receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…We found that CRP, C3, and CFH were associated with brain glucose hypometabolism assessed by FDG in the regions most vulnerable to AD pathology only in APOE ε4 homozygotes (Figure 3). Systemic inflammation and post‐viral infections have been shown to be associated with brain glucose hypometabolism 49–52 . In a mouse model of peripheral inflammation and cerebrovascular damage the brain had low FDG scores, 53 whereas Pang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that CRP, C3, and CFH were associated with brain glucose hypometabolism assessed by FDG in the regions most vulnerable to AD pathology only in APOE ε4 homozygotes (Figure 3). Systemic inflammation and post‐viral infections have been shown to be associated with brain glucose hypometabolism 49–52 . In a mouse model of peripheral inflammation and cerebrovascular damage the brain had low FDG scores, 53 whereas Pang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation and post-viral infections have been shown to be associated with brain glucose hypometabolism. [49][50][51][52] In a mouse model of peripheral inflammation and cerebrovascular damage the brain had low FDG scores, 53 whereas Pang et al demonstrated that apoE mimetic peptides were protective against endothelial damageincreased brain FDG in an animal model of induced subarachnoid hemorrhage. 54 Peripheral insulin resistance has been consistently associated with brain glucose hypometabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Further, GLP2 has a neuroprotective effect and can trigger neurogenesis in a similar manner as GLP1 [ 29 , 37 , 40 , 41 , 42 ]. Interestingly, the anti-inflammatory effects of other components of EEC content have recently been revealed, including PYY [ 43 , 44 ] and serotonin [ 45 , 46 ], which are likely associated with neuroinflammation. Therefore, accumulating evidence suggests that EECs and ECs could play important pathogenic and regulatory roles in neurological and psychiatric disorders.…”
Section: Enteroendocrine Cell Functions That Might Be Related To Neur...mentioning
confidence: 99%